2012
DOI: 10.1007/s10875-012-9667-2
|View full text |Cite
|
Sign up to set email alerts
|

Rare Duplication or Deletion of Exons 6, 7 and 8 in CYBB Leading to X-Linked Chronic Granulomatous Disease in Two Patients from Different Families

Abstract: Chronic granulomatous disease (CGD) is a rare congenital disorder in which phagocytes cannot generate superoxide (O(2)(-)) and other microbicidal oxidants due to mutations in one of the five components of the O(2)(-)-generating NADPH oxidase complex. The most common form is caused by mutations in CYBB on the X chromosome, encoding gp91phox, the enzymatic subunit of the phagocyte NADPH oxidase. Here, we report two rare cases of male X-linked CGD patients, one caused by a 5.7-kb duplication of a region containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Stasia et al. reported two interesting cases of male XR‐CGD patients, one with a 5.7‐kb duplication spanning exons 6 and 8 of CYBB gene and the other with a deletion of the same region. Both mutations are probably caused by a single event of non‐homologous meiotic or mitotic crossing‐over between two high‐similarity short‐tandem‐gene therapy (GT) repeats of introns 5 and 8.…”
Section: Molecular Genetic Aspects Of Cgdmentioning
confidence: 99%
See 2 more Smart Citations
“…Stasia et al. reported two interesting cases of male XR‐CGD patients, one with a 5.7‐kb duplication spanning exons 6 and 8 of CYBB gene and the other with a deletion of the same region. Both mutations are probably caused by a single event of non‐homologous meiotic or mitotic crossing‐over between two high‐similarity short‐tandem‐gene therapy (GT) repeats of introns 5 and 8.…”
Section: Molecular Genetic Aspects Of Cgdmentioning
confidence: 99%
“…So far, large deletions and duplications are considered uncommon genetic mutation events in CGD patients, probably due to the difficulty to detect multiple exon deletions/insertions with conventional methods (sequencing, PCR-SSCP, Southern blot). Recently, array comparative genomic hybridization (array CGH) and multiplex ligationdependent probe amplification were proposed for the detection of copy number variations (26,27) in CGD patients also. Stasia et al (27) reported two interesting cases of male XR-CGD patients, one with a 5.7-kb duplication spanning exons 6 and 8 of CYBB gene and the other with a deletion of the same region.…”
Section: Molecular Genetic Aspects Of Cgdmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in case the indicator patient has a complete deletion of CYBB (on the X chromosome), the mother cannot be defined as a carrier of this deletion by simple gene sequencing. MLPA or array CGH analysis can then be applied .…”
Section: Carrier Detectionmentioning
confidence: 99%